Pemetaan Daya Tarik Wisata dan Fasilitas Penunjang Pariwisata Berbasis Geography Information System di Desa Belimbing, Tabanan-Bali - PRASTUTI, LUH GEDE PINA ADI; SARDIANA, I KETUT; KUSMIYARTI, TATI BUDI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.2, April 2022, 2022)
Mapping of Tourist Attractions and Geograpyh Information System Based Tourism Support Facilities in Belimbing Village, Tabanan-Bali Belimbing Village has potential that can be used as a tourist area, but the development of tourism potential has not been maximized, a lack of utilization, development of natural resources so that it has not been able to provide economic benefits for the community. The purpose of this study was to take an inventory, identify, determine the level of feasibility, and prepare directions for the development of natural potential in Belimbing Village into a tourist area by utilizing the Geography Information System (GIS) application. The method used in this research is the spatial analysis based on attractiveness, supporting facilities, and supporting facilities. Results of spatial data processing and field survey show that Belimbing Village has 3 natural tourism potentials and 1 cultural/religious tourism potential.